Efecto DAM: Diego Armando Maradona en algunas representaciones literarias. - Brescia, Pablo (Funes. Journal of narratives and social sciences, 2022)
Since its arrival to the shores of the River Plate, football has been an integral part in the construction of Argentine national identity. As Pablo Alabarces states, in the last 30 years social and cultural discourses point to a clear phenomenon: “‘footbalization’, meaning that many aspects of Argentine society are discussed in terms of sport”. During that time, Diego Armando Maradona, symbol of the Argentine national team between 1979 and 1994 has been thrown into the spotlight and cast as a representative of such identity, joining fictional and historical figures such as Martín Fierro, Carlos Gardel, Che Guevara and others. For this article I will study the intersection of football, Maradona, and national identity as seen through the lens of literature (fiction and essay). I will then analyze and interpret the different “construction and de-construction” operations around the player Maradona and what does that mean for the dynamics of national identity as related to football.